PEMBUKUAN SECARA PRAKTIS DALAM PENGELOLAAN KEWIRAUSAHAAN EMPING MLINJO DI DESA WONOKERSO, LIMPUNG KABUPATEN BATANG - Agung Wibowo; Caecilia Sri Haryanti; Parju Parju; Nurchayati Nurchayati; Janti Janti; Setyobudi Setyobudi (MAJU : Indonesian Journal of Community Empowerment, 2026)
Mlinjo chip entrepreneurs in Wonokerso Village encountered difficulties managing finances systematically without adequate bookkeeping practices, hindering accurate profit-loss assessment. This community engagement program sought to enhance practical bookkeeping capabilities among fifteen members of "Sumber Rejeki" business collective through comprehensive training and mentoring. The intervention employed participatory methods encompassing preparation, socialization, skill development workshops, continuous guidance, and performance evaluation. Findings demonstrated substantial improvement in financial literacy, evidenced by assessment scores advancing from 42.3 to 81.7. Participants successfully mastered daily transaction recording (100%), income statement preparation (86.7%), and production cost calculation (73.3%). Systematic documentation revealed authentic profit margins of 18-22%, contradicting initial estimations of 30-35%. The initiative yielded multiple benefits including enhanced financial awareness, data-driven decision-making capacity, and improved creditworthiness for institutional financing. Sustainability mechanisms were established through peer mentoring systems and regular accountability sessions within the business network